IL-5, IL-31 and systemic immune-inflammation index as biomarkers predicting severity and progression in bullous pemphigoid - Zhang, Yanyu; Liu, Xia; Hou, Lili; Zhao, Yan; Hao, Jiaxuan; Zhang, Na; Tian, Jing; Li, Xiaoqing; Liu, Zhiyu; Zhou, Hongwei; Xu, Chunyang; Ren, Yuan; et al. (Frontiers in Medicine, 2025)
IntroductionInflammatory mechanisms assume a pivotal role in bullous pemphigoid (BP). IL-31, IL-5, and the systemic immunoinflammatory index (SII) are emerging markers of inflammatory activity, but their associations with BP severity remain unclear. This investigation sought to investigate the correlation of the three aforementioned indicators with BP disease severity to determine their potential application in predicting BP severity.MethodsThis study enrolled 83 BP patients and 50 healthy controls (HC). Patients were stratified into mild-moderate (MM, n = 23) and severe (Sev., n = 60) groups based on body surface area (BSA) involvement. Serum IL-5 and IL-31 levels were measured by Chemiluminescence Immunoassay (CLIA) and ELISA. The SII was calculated as platelets × neutrophils/lymphocytes. Differences between groups were assessed using non-parametric tests, correlations were analyzed using Spearman’s correlation, and predictive performance was evaluated using logistic regression and ROC curves. Five patients underwent longitudinal IL-31 and IL-5 measurement pre- and post-treatment.ResultsInterleukin-31 and IL-5 levels were significantly raised in BP versus HC (median [Q1–Q3]: IL-5: 2.86 [1.22–7.10] vs. 0.79 [0.65–1.00] pg/mL; IL-31: 103.61 [77.42–146.77] vs. 86.02 [51.49–122.53] pg/mL), with further increases in Sev. versus MM groups (IL-5: 3.84 [1.57–10.63] vs. 1.35 [0.83–2.93] pg/mL; IL-31: 125.99 [91.58–173.85] vs. 65.14 [51.27–85.47] pg/mL). Post-treatment IL-31 decreased significantly in 5 patients (145.95 ± 44.25 vs. 108.62 ± 33.45 pg/mL). IL-5, IL-31, and SII positively correlated with BSA (r = 0.458, 0.544, 0.418). Logistic regression analysis identified elevated levels of IL-5, IL-31, and SII as risk factors for the exacerbation of BP disease. ROC analysis demonstrated the remarkable predictive capacity of IL-5, IL-31, and SII for BP disease severity.ConclusionInterleukin-5, IL-31, and SII are promising biomarkers for assessing and predicting BP severity.